The Effect Of Non-Debt Tax Shield, Asset Structure And Growth Opportunities On Capital Structure With Compa-ny Size As Moderating Variable - Maria Gratia; Arum Prastiwi (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
The debt-to-equity ratio serves as a key indicator for assessing a company's financing policy. Rising interest rates increase the cost of debt, thereby influencing corporate financing decisions. This quantitative study aims to examine the effect of non-debt tax shield, asset structure, and growth opportunity on the debt-to-equity ratio of infrastructure companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period, with firm size acting as a moderating variable. The sample selection was conducted using the purposive sampling method, resulting in 104 observations. The data were analyzed using SPSS version 25. The results show that non-debt tax shield has a negative effect on the debt-to-equity ratio, while asset structure has a positive effect on the debt-to-equity ratio. Firm size weakens the negative effect of non-debt tax shield on the debt-to-equity ratio and strengthens the positive effect of asset structure on the debt-to-equity ratio. On the other hand, growth opportunity does not affect the debt-to-equity ratio, and firm size does not moderate the relationship between growth opportunity and the debt-to-equity ratio. These findings highlight the importance of carefully managing the debt-to-equity ratio to ensure that financing decisions support the company's financial stability.